The West African trade outlook: Business-as-usual compared with alternative options - Odjo, Sunday P.; Badiane, Ousmane (International Food Policy Research Institute, 2018)
Chapter 7, by Sunday Pierre Odjo and Ousmane Badiane, focuses on the outlook for expanding intra-regional trade within West Africa, the focus region of this issue, and the potential effects of expanded trade on regional food markets. The chapter reviews recent trends in intra-regional trade and examines the possibilities for increased regional trade to reduce food price volatility. The study then evaluates the scope for increasing trade within the region. A simulation model is used to examine the effects of alternative policy scenarios on regional trade and on the stability of regional food markets.